Dietary supplementation of curcumin ameliorate aflatoxn B1 induced oxidative stress in mice (Journal of Laboratory Animal Science, 2018)
Studies were carried out to evaluate the effect of dietary supplementation of curcumin on toxicopathology of  aflatoxicosis in laboratory mouse following short-term exposure to aflatoxin B1. Sexually matured Swiss albino  mice of either sex weighing between 28-30g were divided into two groups consisting of six animals each.  Animals in group I (positive control) were fed with aflatoxin B1 mixed in standard rodent chow (7.5 ppb) and  group II (treatment) received aflatoxin B1 (7.5 ppb) along with curcumin (1g/kg feed) for a period of 14 days.  At term, oxidative stress and hepatotoxicity were assessed by determining tissue and serum specific enzymes  and by histopathology. Short term exposure to aflatoxin-B1 significantly (P< 0.05) decreased hepatic GSHr levels on account of oxidative stress as evidenced by elevated TBARS levels (group I). However, concomitant  administration of curcumin has significantly (P< 0.05) reduced the TBARS and protected depletion of hepatic  GSHr levels. Curcumin supplementation (group II) has markedly reduced the toxicopathological lesions in  liver induced by aflatoxin B1 and consequent reduction (P< 0.05) in serum levels of both aminotransferase  (s) and phosphatase. Thus, the present study demonstrated the potential benefits of dietary supplementation of  curcumin in ameliorating aflatoxin induced oxidative stress in mice
Keywords: aflatoxin-B1; curcumin; lipid peroxidation; mice and toxicopathology